Activating transcription factor 2 (ATF2) negatively regulates the expression of antimicrobial peptide genes through tumor necrosis factor (TNF) in Macrobrachium nipponense. Issue 107 (December 2020) - Zhang, Chao; Zhang, Ruidong; Dai, Xiaoling; Cao, Xueying; Wang, Kaiqiang; Huang, Xin; Ren, Qian
Abstract: Activating transcription factor 2 (ATF2), a member of the bZIP transcription factor family, is involved in multiple physiological and developmental processes, yet its role in the innate immunity remains unclear. In this study, two isoforms (named as MnATF2a and MnATF2b ) of ATF2 gene were identified in Macrobrachium nipponense and were produced by exon skipping. The full length of MnATF2a is 2328 bp with an open reading frame of 2079 bp that encode 692 amino acids. MnATF2a has 237 bp nucleotides more than MnATF2b and the extra 237 bp is a complete exon. MnATF2a and MnATF2b proteins contain the same conserved and typical bZIP domain at the C-terminus. MnATF2a has 79 amino acids more than MnATF2b. MnATF2a and MnATF2b are widely distributed in a variety of immune tissues. After Vibrio parahaemolyticus and Staphylococcus aureus infection, the expression levels of MnATF2a and MnATF2b were significant up-regulated in the gills and stomach at 12 h. RNA interference analysis showed that knockdown of the total MnATF2 gene significantly inhibits the transcription of tumor necrosis factor ( TNF ) and promotes the expression of crustins (including Cru3, Cru4, and Cru7 ). Further study showed that knockdown of MnTNF evidently increase the expression of Cru3, Cru4, and Cru7 . Our research indicates that ATF2 negatively regulate the expression of AMPs by regulating the transcription of TNF in M. nipponense . This study provides valuable information about the function of ATF2 family in the innate immunity in crustacean. Highlights: Two isoforms of ATF2 gene were found in Macrobrachium nipponense . The expression of MnATF2a and MnATF2b were increased after Vibrio parahaemolyticus and Staphylococcus aureus infection. MnATF2 can positively regulate the expression of MnTNF . MnATF2 and MnTNF can negatively regulate the expression of AMPs.